2013
DOI: 10.1126/science.1234393
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Evolution of Essential Centromere Function in a Drosophila Neogene

Abstract: Evolutionarily young genes that serve essential functions represent a paradox since they must perform a function that either was not required until after their birth or was redundant with another gene. How young genes rapidly acquire essential function is largely unknown. Here, we trace the evolutionary steps by which the Drosophila gene Umbrea acquired an essential role in chromosome segregation in D. melanogaster, since its origin less than 15 million years ago. Umbrea neofunctionalization occurred via loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 38 publications
4
120
1
Order By: Relevance
“…It has been previously hypothesized that genes that encode proteins interacting strongly with heterochromatin can be potential actors of genetic conflicts (10,15,19,23). We show here for the first time, to our knowledge, that such a gene, expressed in the male germ line, plays a key role in an extended intragenomic conflict in D. simulans.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It has been previously hypothesized that genes that encode proteins interacting strongly with heterochromatin can be potential actors of genetic conflicts (10,15,19,23). We show here for the first time, to our knowledge, that such a gene, expressed in the male germ line, plays a key role in an extended intragenomic conflict in D. simulans.…”
Section: Resultsmentioning
confidence: 66%
“…However, because HP1D2 SR localizes to the Y chromosome as well, we cannot exclude that CSD-lacking HP1D2 proteins cause drive through aberrant interactions with other chromatin proteins. If it is the case, CSD-lacking HP1D2 may evolve a new function, which has been described for another HP1 (23).…”
Section: Hp1d2 Ismentioning
confidence: 99%
“…Also notably, the CMS gene origination processes from the protogene orf367 to the functional genes WA352a/b/c and WA314 were completed within a relatively short timeframe in O. rufipogon (less than two million years [19]). This process appears to be much faster than the origination of most nuclear new genes, such as the new Drosophila gene Umbrea whose origination has spent 15 million years [45], thus reflecting the remarkably dynamic properties of plant mitochondrial genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of genome sequences from many organisms has revealed that gene duplication followed by retention of two functional copies is widespread (for reviews, see Prince and Pickett 2002;Long et al 2003; see also Chen et al 2010;Ross et al 2013). According to classical models, duplicated genes can have two main fates.…”
Section: Discussionmentioning
confidence: 99%